Efeito de um programa de natação e ginástica respiratória sobre a ativação de músculos acessórios da respiração em asmáticos - Silva, Marta Cristina Rodrigues da (2014)
Introduction: Asthma is a chronic airway that causes airflow obstruction inflammatory disease. This leads to hyperinflation, causing the individual to use intensively the accessory muscles of respiration. Swimming and respiratory gymnastics are ideal exercises for the asthmatic individual. Objective: To analyze the effects of an exercise program on the activation of accessory muscles of respiration and the maximal respiratory pressures. Methodology: The study included 10 asthmatic subjects, with a mean age of 10.70 ± 2.45 years. The protocol consisted of a 4-month program of swimming and respiratory fitness. The electrical activity of the sternocleidomastoid (ECM) and trapezius (TRZ) was measured by EMG and evaluated by the Root Mean Square (RMS) values normalized to the analysis of maximal inspiration. Maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) were evaluated by means of a manometer. There was a descriptive analysis of data and normality was tested the same using the Shapiro-Wilk test. To check for differences in variables analysis of variance was used. For normal data was used for repeated measures ANOVA with post hoc LSD, and for non-normal data was used Friedman ANOVA with post hoc Wilcoxon. The statistical package used was SPSS for Windows version 14.0, with a significance level of 5%. Results: The results showed significant difference after the program with decreased muscle activation for both ECM at maximal inspiration (p <0.01) and rest (p = 0.01), as for the TRZ at maximal inspiration (p = 0, 02) and rest (p <0.01). The maximum respiratory pressures only difference was in MEP (p = 0.01).Conclusion: The swimming program and respiratory fitness caused a decreased activation of accessory muscles of respiration and improves MEP, demonstrating the efficiency of the program.